2016
DOI: 10.1038/srep25886
|View full text |Cite
|
Sign up to set email alerts
|

Changes in inflammatory cytokine networks in myasthenia gravis

Abstract: Myasthenia gravis (MG) is an autoimmunological inflammatory disorder of the neuromuscular junction. Inflammation could be a key player for understanding the pathogenesis of MG. We measured the serum levels of 24 inflammatory cytokines in 43 patients with anti-acetylcholine receptor antibody-positive MG and 25 healthy controls. In patients with MG, serum levels of a proliferation-inducing ligand (APRIL), IL-19, IL-20, IL-28A and IL-35 were significantly increased as compared with controls (p < 0.05). Among them… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
46
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 25 publications
1
46
0
5
Order By: Relevance
“…Astrocytes produce IL-19 in response to bacterial challenge and significantly attenuate inflammation [19]. Interestingly, accumulating evidence recognizes IL-19 as an important player in the pathogenesis of other autoimmune diseases such as asthma, rheumatoid arthritis, and myasthenia gravis [20,21,22]. IL-19 may exert diverse properties on different cell types, including monocytes, macrophages, and microglia [18], and has anti- or proinflammatory functions in different inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Astrocytes produce IL-19 in response to bacterial challenge and significantly attenuate inflammation [19]. Interestingly, accumulating evidence recognizes IL-19 as an important player in the pathogenesis of other autoimmune diseases such as asthma, rheumatoid arthritis, and myasthenia gravis [20,21,22]. IL-19 may exert diverse properties on different cell types, including monocytes, macrophages, and microglia [18], and has anti- or proinflammatory functions in different inflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Both miR-150-5p and miR-21-5p are involved in the regulation of the autoimmune response, and in particular the development of T- and B-cells. One recent study on inflammatory proteins in MG revealed significantly increased serum levels of a proliferation-inducing ligand (APRIL), and cytokines IL-19, IL-20, IL-28A and IL-35 in MG as compared with controls13. Otherwise, no previous study has focused on defining a broad inflammatory circulating protein profile in MG patients and in different clinical MG subtypes.…”
mentioning
confidence: 99%
“…в нервно-мышечных структурах [101,103,115]. В качестве посредников они принимают участие в дифференцировке иммунокомпетентных и гемо-поэтических клеток, в формировании механизмов межклеточного взаимодействия, лежащих в осно-ве иммунного ответа.…”
Section: роль цитокинов в патогенезе миастении грависunclassified
“…Основная их биологическая активность -регуляция иммунного ответа на всех этапах его развития [117]. В целом следует отметить, что вся эта большая груп-па эндогенных регуляторов участвует в делении и дифференцировке клеток-предшественников функционально активных иммунокомпетентных клеток, изменении экспрессии антигенов и различ-ных маркеров, хемотаксисе, переключении синте-за иммуноглобулинов, индукции цитотоксичности у макрофагов, пролиферации антиген-чувствител ь-ных лимфоцитов, дифференцировке В-клеток в про-дуценты иммуноглобулинов, переключении синтеза иммуноглобулинов с одного изотипа на другой, обе-спечении созревания предшественников цитоток-сических Т-клеток до зрелых эффекторов, индукции цитотоксичности у макрофагов, формировании оча-га воспаления [101,103]. Цитокины при этом играют координирующую роль в патогенезе аутоиммунных заболеваний, они при-нимают участие во взаимодействиях В-лимфоцитов и Т-хелперов (Th) [15].…”
Section: роль цитокинов в патогенезе миастении грависunclassified
See 1 more Smart Citation